KORELASI PEMAHAMAN KONSEPTUAL DENGAN PEMAHAMANPROSEDURAL SISWA MELALUI PEMBELAJARAN MATEMATIKA REALISTIK DI SMP - Pandini, Wayan Arum; Rif’at, M; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to analyze data about student’s conceptual understanding, properties of rhombus and parallelogram and procedure comprehension to fine the area. Furthermore, the purpose of this research is to know about correlation between: 1) conceptual understanding and the properties of rhombus and paralellogram; 2) conceptual understanding and procedural comprehension of rhombus and parallelogram, and 3) the properties and procedural comprehension to fine the area. Research method that be used is experiment research method. The experiment was give treatment after realistic mathematic learning in the form of a posttest for student individually. The research sample is students in class VII E. The selection of students to be the sample of research based on school’s consideration and teacher’s recommendation. Based on statistic test, the conclusions of this research are: 1) there is correlation between student’s conceptual understanding and properties of rhombus and parallelogram to fine the area; 2) there is correlation between student’s conceptual understanding and procedural comprehension to fine the area; and 3) there isn’t correlation between student’s properties comprehension and procedural comprehension of rhombus and parallelogram to fine the area. Keywords: Conceptual Understanding, Procedural Comprehension and Realistic Mathematic Education